Dual career athletes and psycho-physiological stress - Francesca Latino; Pierpaolo Limone; Francesco Peluso Cassese; Rosabel Martinez-Roig; Giulia Amato; Francesco Tafuri (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: The high-level athletic careers frequently conclude significantly earlier than those in other fields, and at times, despite the considerable efforts exerted, they do not consistently flourish as anticipated. Consequently, numerous athletes concurrently pursue academic pathways to adequately prepare for alternative professional opportunities beyond the realm of sports.  Objective: Accordingly, the objective of the current investigation was to examine the efficacy of Yoga in ameliorating the stress levels experienced by student-athletes.